Crash behaviour and performance of long fibre reinforced thermoplastic material in comparison with continuous fibre reinforcement. Issue 4 (4th July 2018) - Jung, Gihune; Schmeer, Sebastian; Mitschang, Peter
ABSTRACT: Multi-layered hybrid mat (MLH-mat) is a long fibre reinforced thermoplastic material with a high glass fibre content of around 45 vol. % and with inherent flowability. Crash behaviour and performance were investigated and compared with those of continuous fibre reinforcement. Dynamic tests were conducted on welded round-hat tubes with impact velocities over 8 m/s. PP/GF MLH-mat showed 44 J/g for specific energy absorption (SEA) and 63 MPa for mean stress, equivalent to continuous fibre reinforcement in performance. By changing matrix polymer, PA6/GF MLH-mat could obtain higher crashworthiness of 51 J/g for SEA and 84 MPa for mean stress; 15% higher in SEA compared to PP/GF MLH-mat. This enhancement is mainly related to longer strain and higher modulus as well as higher melting temperature of matrix polymer. The crash behaviour of MLH-mat fulfils the mode of 'splaying and lamina-bending followed by inside-wrinkling and outside-tearing' with more gentle deformation.